PELAKSANAAN PERATURAN DAERAH NOMOR 11 TAHUN 2008 TENTANG ALOKASI DANA DESA DI KECAMATAN LIBURENG KABUPATEN BONE - Andi Kasmawati; Melindah Melindah (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2018)
This study aims to determine (1) Implementation of Regional Regulation No. 11 of 2008 on the Village Fund Allocation In District Libureng Bone regency. (2) Barriers in Implementing Regional Regulation No. 11 of 2008 on the Village Fund Allocation In District Libureng Bone regency. To achieve these objectives, the researchers used a technique of collecting data through interviews and documentation. This research is a qualitative descriptive study. Sources of data used consist of primary data and secondary data. Data have been obtained from the results of the study were processed using qualitative analysis to determine Implementation of Regional Regulation No. 11 of 2008 on the Village Fund Allocation In District Libureng Bone regency, and Barriers in the Implementation of Regional Regulation No. 11 of 2008 on the Village Fund Allocation In District Libureng Bone District , The results showed that: (1) Implementation of Regional Regulation No. 11 of 2008 concerning Village Allocation Fund (ADD) in District Libureng Bone regency runs quite Good. It can be seen from the planning stage in the form of personnel administration has to be consulted in planning ADD, and do manufacture RPJMDes, as well as the manufacture RKPDes As local regulation of ADD can be a direction to the Executive Team Village in running ADD both in terms of allocation of funds and purpose of use fund. (2) Some of the obstacles encountered in the implementation ADD ie reporting of accountability and weather conditions in the village as the rainy season may hamper the implementation of the development undertaken. Every problem that they get in the process of implementation of ADD in his village can selesaikannya with their guidance and consultation with pihal-parties, such as team Pembina Pembina district and sub-district level teams.